(3JjSjQ GdhUhd Edi LGeY GdCUhds - (3YHO GdQMef Hf Ydj Hf eMeO Hf YeQ GdOjHY GdTjHGfis; (3GdeHGQc Hf eMeO Hf eMeO Hf eMeO GHf nYrHO GdncpQje GdTjHGfqj GdLRQj, CHh GdSYGOGJ, eLO GdOjf, GHf GdCKjQ,J (B606 (3g` s ((3CMeO Hf bGSe Hf Ydi Hf bGSe GdYRhi GdTjHGfi s)
(3ChdgG (B:s
(3jHOC HcJGH GdUhe (B" (3bhdg hajg KdGKI CHhGH , GdHGH GdChd ai aVdg haVd TgQ QeVGf , Yf CHj gQjQI s
(3BNQgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde (B:" (3cdeJGf NajaJGf Ydi GddSGf KbjdJGf ai GdejRGf MHjHJGf Edi GdQMef SHMGfg Gddg hHMeOg SHMGf Gdg GdYXje , BNQ GdLRA GdKGfi hHJeGeg Je LejY GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3GdfSNI ebGHdI Ydi fSNI ebGHdI Ydi fSNI GdeDdas
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfhGfGJ HGdMeQIs
(3cJHJ HQSe GdTjN LeGd GdOjf eMeO Hf CSMe s
(3hYdjgG SeGYGJ hJedcGJ eJbOeI s
Keywords: (3GdMOjK h GdeUWdMs